Immediate Effects of Dry Needling vs. Functional Dry Needling in Patients with Shortened Calf Muscles - Muhammad Taha Javed, Samraiz Mughal, Ayesha Rani, Kinza Jabbar, Zahra Kanwal, Zainab Nadeem, Muhammad Khurram Fiaz, Hamza Qamar (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Shortened muscle is a condition of physical shortening of the length of the muscle and is also accompanied by other soft tissues surrounding the muscle. In shortened calf muscles the muscles (gastrocnemius and soleus) of lower leg have reduction in their length resulting in pain, reduced range of motion of joint and somehow limiting the functional ability and capability of and individual. The use of dry needling as well as functional dry needling is thought to reduce pain and increase range of motion. Objective: This study was aimed at finding the immediate effects of dry needling versus functional dry needling on pain and range of motion. Methods: It was a quasi-experimental study conducted at Buch International Hospital, Multan & Ali Rehabilitation & pain relief center, Multan from February 01, 2023, to April 31, 2023. There were two groups in total. One group was provided with functional dry needling and the other with dry needling. Only single session was taken and measurements of Numeric Pain Rating Scale and range of motion with goniometry were recorded before and after the treatment. SPSS-27 was used to analyze the data. Results: There were a total of 40 patients. 20 patients were assigned to functional dry needling group and 20 patients to dry needling group. The mean age of patients was 27.65 + 2.368 and 27.80 + 1.852 in functional dry needling and dry needling groups respectively. Pain severity in functional dry needling group reduced significantly compared to dry needling group at the end of the session (p-value=<0.01). Active range of motion and passive range of motion were found non-significant at the end of session (p-value=.089 and p-value=.146) respectively. Conclusion: Both functional dry needling and dry needling reduces pain severity but functional dry needling resulted in reduction in pain severity more than dry needling whereas, both showed non-significant effects on range of motion. Keywords: FDN; functional dry needling, DN; dry needling, AROM; active range of motion, PROM; passive range of motion.